2020
DOI: 10.3390/cancers12123864
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-Derived Leptin Promotes PAI-1-Mediated Breast Cancer Metastasis in a STAT3/miR-34a Dependent Manner

Abstract: The crosstalk between cancer cells and adipocytes is critical for breast cancer progression. However, the molecular mechanisms underlying these interactions have not been fully characterized. In the present study, plasminogen activator inhibitor-1 (PAI-1) was found to be a critical effector of the metastatic behavior of breast cancer cells upon adipocyte coculture. Loss-of-function studies indicated that silencing PAI-1 suppressed cancer cell migration. Furthermore, we found that PAI-1 was closely related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 73 publications
(131 reference statements)
0
13
0
Order By: Relevance
“…Plasminogen activator inhibitor-1 (PAI-1) is a serine protease inhibitor encoded by the serpin family E member 1 gene ( 16 ). PAI-1 was found to be upregulated in a variety of different tumors, such as breast ( 17 ), ovarian ( 18 ) and colon cancers ( 19 ), and possess several pro-tumorigenic functions, including supporting proliferation and angiogenesis, inhibiting cell apoptosis and promoting metastasis ( 17 , 18 , 20 ). Along with cancer cells, several other components of the TME, including platelets, macrophages and vascular cells, also secrete PAI-1 ( 16 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plasminogen activator inhibitor-1 (PAI-1) is a serine protease inhibitor encoded by the serpin family E member 1 gene ( 16 ). PAI-1 was found to be upregulated in a variety of different tumors, such as breast ( 17 ), ovarian ( 18 ) and colon cancers ( 19 ), and possess several pro-tumorigenic functions, including supporting proliferation and angiogenesis, inhibiting cell apoptosis and promoting metastasis ( 17 , 18 , 20 ). Along with cancer cells, several other components of the TME, including platelets, macrophages and vascular cells, also secrete PAI-1 ( 16 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…After the activation of PI3K/AKT in the breast cancer cells, the expression of IL-6, IL-1β, and tumor necrosis factor-α (TNF-α) in breast cancer cells is increased [ 131 ]. Leptin can also promote plasminogen activator inhibitor-1 expression, which is related to EMT, by activating STAT3 to promote metastasis [ 132 ]. Free fatty acids (FFAs) [ 133 ], monocyte chemoattractant protein-1 (MCP-1) [ 134 ], CC-chemokine ligand 5(CCL5) [ 135 ], and insulin-like growth factor 1 (IGF-1) [ 136 ] secreted by CAAs can induce breast cancer cells to be more invasive or more proliferative.…”
Section: Cell Interactions Contribute To Breast Cancer Heterogeneitymentioning
confidence: 99%
“…An orthotopic implantation metastasis model further revealed that plasminogen activator inhibitor-1 (PAI-1) is required for breast cancer metastasis. Mechanistically, the upregulation of PAI-1 expression was elicited by leptin-LEPR-miR-34a axis-mediated STAT3 signaling activation [53]. Leptin also elicits metabolic reprogramming in breast cancer.…”
Section: Leptin and Breast Cancermentioning
confidence: 99%
“…The demonstrations of main biological effects (Table 2) and signaling axes (Figure 4) induced by leptin/leptin receptor in different cancer types were shown. Ovarian Cancer ↑: [41] ↑: [38][39][40]42] ↑: (paclitaxel/docetaxel) [36] Brain Tumor ↑: [45,46] ↑: [47,48] ↑: [45] ↑: (temozolomide) [49] Breast Cancer ↑: [54,58] ↑: [53,55] Liver Cancer ↑: [60,63] ↑: [60,63] ↓: [63] ↓: [65] (rat)…”
Section: Leptin and Other Types Of Cancermentioning
confidence: 99%